IMPLEMENTASI CONTRACT FARMING MODELS PADA SKEMA SUPPLY CHAIN USAHA PENGGEMUKAN TERNAK DOMBA DI KABUPATEN LANGKAT - Marisa, Julia; Wibowo, Fachrina; Kurniawan, Ridho (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Langkat Regency has an excellent opportunity to carry out the sheep farming business process, but it does not rule out the possibility that in carrying out business activities, there are several obstacles that hinder the process. This obstacle is the performance of sheep farming in carrying out business development, in general, is still low, which will affect business competitiveness. The purpose of this research is to analyze the implementation of contract farming models in the research area. Data collection techniques include several techniques, namely using questionnaires through Focus Group Discussions (FGD), in-depth interviews with respondents, document analysis, informal discussions, and direct observation. The data analysis method used is Contract Farming Partnership Analysis. The results showed that the implementation of contract farming models in the study area showed that the supply chain performance results from the reliability attribute only reached an advantage position, so the performance of the supply chain for fattening sheep had to be further improved.